Natural Distribution and Status of Regeneration of Gymnosperms in Arunachal Pradesh - Beniwal, B. S.; Haridasan, K. (Indian Forester, 1992)
The paper deals with 33 species of Gymnosperms belonging to 18 genera and 8 families. The paper discussess the distribution and state of regeneration of Gymnosperm forests in Arunachal Pradesh. In the enumeration, a list of species arranged under each family are provided with their distribution and regeneration status. Apart from wild species references are also made to exotic and introduced species and their prospects in the State's forestry. This is the first such attempt for the North-eastern State which has the highest number of Gymnosperm species.